Harmonizing Algorithms and User Satisfaction: Evaluating The Impact of Spotify's Discover Weekly on Customer Loyalty - Natasha Janice; Nurrani Kusumawati (Journal Integration of Management Studies, 2024)
Integrating artificial intelligence (AI) in music streaming platforms has significantly transformed user experiences, with personalized features playing a key role. This study investigates the impact of Spotify's "Discover Weekly" feature on Indonesian users' satisfaction and customer loyalty. The research examines how the quality of service experience, perceived usefulness, and user engagement interplay to influence the effectiveness of "Discover Weekly" in enhancing user experience and fostering loyalty to Spotify. Using a mixed-methods approach, the study utilizes qualitative analysis through automated coding with Nvivo software (18 respondents) and quantitative analysis using Partial Least Squares Structural Equation Modeling (PLS-SEM) with 397 respondents. The target demographic is Generation Z, familiar with or using the "Discover Weekly" feature. Findings reveal a significant positive impact of service quality experienced through "Discover Weekly" on user satisfaction and subsequent loyalty to Spotify. Additionally, there is a strong positive relationship between user satisfaction and word-of-mouth promotion, suggesting that satisfied users are more likely to recommend "Discover Weekly" to others. Recommendations include enhancing playlist discoverability, refining music content, and encouraging positive word-of-mouth promotion. Future research should explore personalized playlists on other platforms, analyze different demographic profiles, and evaluate additional features offered by Spotify to provide a broader understanding of user experience and loyalty dynamics.